The Ambiguous Migrant. A Profile of African Refugee Resettlement and Personal Experiences in Southeast Queensland, Australia - Claudio, Fernanda (Diversité urbaine)

(untitled) (Groupe de recherche diversité urbaine, 2014)
Australian history is marked by immigration control and attempts to exclude foreigners. Exclusionary strategies toward foreigners are expressed in policies that limit numbers and types of migrants and foster exclusionist attitudes amongst the population. Successive Australian prime ministers have won elections based on policies of immigration and border control. Fear and rejection of foreigners characterize current policies toward asylum seekers and refugees; importantly, this stance also affects the allocation of resources to support refugee resettlement. I examine the implications of underfunding health and social support services for African refugees in Brisbane. A profile of this population is provided along with a discussion of resettlement services. Abdominal pain and inadequate responses by the health system serve to exemplify the complex experiences of newcomers who have not yet found their place in Australia.